Impact of quercetin and gallic acid on the electronic, structural, spectroscopic, thermal properties and in vitro bioactivity of silver-modified hydroxyapatite - Keser, Serhat; Firat, Melikehatun; Barzinjy, Azeez A.; Kareem, Rebaz Obaid; Ates, Tankut; Ates, Burhan; Kaygili, Omer (Elsevier Science Sa, 2025)
Hydroxyapatite (HAp) possesses outstanding characteristics, for instance biocompatibility and osteoconductivity, which are vital for bone reconstruction. Nevertheless, it remains passive against infectious bacteria that can cultivate in compromised bone tissue, and its usage in some individuals under care might result in some objectionable provocative responses. Gallic acid (GA) and quercetin (Que) are recognised for their explicit biological activites. Connecting these properties with silver-modified HAp is remarkably interesting. The current study examined the preparation of un-doped HAp and Ag-based samples in the presence of various extents of GA and Que using the neutralization method at room temperature. The impact of GA and Que on the electronic, structural, thermal, spectroscopic, and biocompatibility properties of HAp and Ag-modified HAp were investigated intensively. Also, mouse fibroblast (L929), human osteoblast (hFOB 1.19), human bone cancer (MG-63) and human colon cancer (Caco-2) cell lines obtained from the ATCC were used for cytotoxic and biocompatibility assays. The bandgap of the distinct regions (occupation of Ca(I) and Ca(II) sites) using DFT were 3.837 and 4.211 eV, respectively. This study showed that introducing Ag as a dopant reduced the bandgap dramatically. X-ray diffraction analysis revealed that the as-prepared samples possess polycrystalline structure. While, the lattice parameters and volume of the unit cell were increased after adding Ag as a dopant. However, both GA and Que containing samples, remarkably decrease these parameters. Both FTIR and Raman spectroscopy utilized to investigate the nature of bonding structure for the utilized samples. It has been shown that the addition of Ag into the HAp causes an increase in the specific heat capacity. SEM images and EDX analysis confirm the distribution of the utilized elements and the purity of the samples. Overall, the prepared Ag-HAp/GA and Ag-HAp/Que samples offered structural and chemical characteristics close to those of ordinary bone that make them a good candidate for bone tissue regeneration.
Keywords: Hydroxyapatite (HAp); Silver (Ag); Quercetin (Que); Gallic acid (GA); Density Functional Theory (DFT)